Monetary policy and macroprudential regulation with financial frictions - Agénor, Pierre-Richard, (MIT Press, 2020)
"A monograph that accounts for financial frictions in some of the most-used macroeconomic models. An attempt to bring practical reality into macroeconomic theory"--